IDENTIFIKASI JENTIK NYAMUK, KARAKTERISTIK SUMUR GALI DI KELURAHAN AIR DINGIN KOTA PEKANBARU 2019 - Beny Yulianto (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2020)
Infectious diseases that are still prioritized given their contagious nature and cause harm, one of that is Dengue Hemorrhagic Fever (DHF). Clean water facilities use by the community for daily needs, that called wells. This study aims to identification types of mosquito larvae and characteristic of wells on the society. The type of research is a descriptive study with a survey approach. This research conducted at Air Dingin District on February 2019 with amount of samples are 63 wells.Collecting data use checklist sheet, larvatrap and ph meter. The analysis data use is univariate analysis. The results showed that from 63 wells, 11 wells had larvae, the types of larvae identified were aedes alboqpictus, the location of the wells were mostly inside the house, deep of wells are 5.1-15 meters and>15 meters, the condition of wells were mostly open, the degree of acidity (pH) is neutral condition (pH 7). The wells that are owned by the community in Air Dingin district can be a breeding ground for mosquito larvae. Suggestion for society is can close the wells closely and can use predators to prevent the larvae.